CULTURAL CONSTRUCT AND IDENTITY IN THE SELECTED WORKS OF THREE FEMALE DIASPORIC AUTHORS : Received: 24th September 2021; Revised: 13th December 2021, 12th March 2022, 9th April 2022; Accepted: 13th April 2022 - Badhwar, Devina (PEOPLE: International Journal of Social Sciences, 2022)
The primary concern of this paper is to engage in a critical inquiry on the issue of identity in the literature of the diaspora by three selected writers Chitra Banerjee Divakaruni, Jhumpa Lahiri, and Bharati Mukherjee. An identity crisis is not a product of any singular circumstance or reason. There can be multiple factors contributing to the crisis of identity in an individual. It is important to note here that not only the source but also the manifestation of the crisis is varied, in the sense that individuals differ in their ways of internalizing, as also, externalizing, the emotions attached to his/her identity- as a man/woman; as a citizen; as a professional; as a part of the system of beings, etc. My concern, however, is with the loss of identity as a consequence of the loss of culture. I propose that settlements in foreign lands (away from one’s birthplace/ native land) are bound to breed a sense of identity loss since there has been, willy-nilly, a loss of cultural identity while trying to fit in into a new land/social surrounding—and the culture thereof.